Data in Crisis: anticipating risk, vulnerability, and resilience through communication infrastructures - Katrina Petersen; Agata Gurzawska (communication +1, 2021)
This paper explores the implications of having interactions around crises progressively based in information and communication technology (ICT), data, and their infrastructures. Drawing on applied research from multidisciplinary projects to design crisis ICT, we describe the how these tools become fundamental to how crisis communication and governance can and does work. Crisis ICT facilitate collaboration and interoperability in ways that make it possible for crisis managers to share each other’s strategies, processes, goals, and perspectives. They also bring together different histories of risk assessment practices and socio-political situations. Combining them meaningfully requires anyone working with the ICT to actively negotiate and deliberate what that combined view includes. We examine a series of tensions raised by infrastructuringdiverse crisis data and discuss what they mean for conceptions of crisis risk, vulnerability, and resilience. First, are tensions that emerge when trying to provide an underpinning logic that makes data shareable and comparable. Second, are the dynamics that come from misunderstandings as crisis practitioners from different disciplines and cultures engage with each other through these infrastructures. Third are the tensions raised through the anticipatory conflicts between concrete data needs of a technology and the uncertainties of how crises unfold. Finally, we consider how these infrastructures stabilise crises to make them visible, actionable, and contestable. We argue that crisis communication requires reflexive perspectives, building into all communication practices mechanisms by which actors can be mutually responsive to each other. Our aim is to provoke those engaging with such tools to consider how risk, vulnerability, resilience, and the lived experience of crises are intertwined with the infrastructures that make communication possible.